2003
DOI: 10.1097/01.hjr.0000106836.97722.cf
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of electrocardiographic left ventricular hypertrophy to mortality and cardiovascular morbidity in high-risk patients

Abstract: In patients with CV disease simple, easily applicable ECG criteria for LVH identify a subset of individuals at particularly high risk for death and for heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Left ventricular (LV) hypertrophy on electrocardiography or increased left ventricular mass (LVM) on echocardiography are strong predictors of death and nonfatal cardiovascular events in patients with hypertension, coronary heart disease, other cardiovascular diseases, and in the general population (1)(2)(3)(4)(5). Moreover, similar to other cardiovascular risk factors,…”
mentioning
confidence: 99%
“…Left ventricular (LV) hypertrophy on electrocardiography or increased left ventricular mass (LVM) on echocardiography are strong predictors of death and nonfatal cardiovascular events in patients with hypertension, coronary heart disease, other cardiovascular diseases, and in the general population (1)(2)(3)(4)(5). Moreover, similar to other cardiovascular risk factors,…”
mentioning
confidence: 99%
“…The Heart Outcomes Prevention Evaluation (HOPE) trial examined the predictive value of Sokolow-Lyon voltage criteria in 9541 adults with established CV disease [5]. Patients meeting criteria for LVH had higher mean blood pressures than those without ECG LVH.…”
Section: Prognostic Implications Of Ecg Lvhmentioning
confidence: 99%
“…The HOPE trial demonstrated a potent relationship between Sokolow-Lyon voltage and HF [5]. In addition, given the relation of ECG strain and disease severity, it is not surprising that ECG strain predicts the development of HF.…”
Section: Heart Failurementioning
confidence: 99%
“…The resting electrocardiogram (ECG) is a simple, noninvasive and widely applicable method, useful for diagnosing of left ventricular hypertrophy (LVH) in different populations [1][2][3][4][5]. Numerous studies have documented electrocardiographic LVH to be a harbinger of greater morbidity and mortality, especially in patients with coronary artery disease [6].…”
Section: Introductionmentioning
confidence: 99%
“…For clinical purposes voltage-based ECG criteria, like Sokolow -Lyon or Framingham, have relatively low sensitivity for detection of increased left ventricular mass (LVM) [8,11,13,17]. However, despite their limitations, these indices are still employed in recent studies, especially in hypertensive patients [4,16].…”
Section: Introductionmentioning
confidence: 99%